GNE myopathy: History, etiology, and treatment trials - Mullen, Jeffrey; Alrasheed, Khalid; Mozaffar, Tahseen (Frontiers in Neurology, 2022)
GNE myopathy is an ultrarare muscle disease characterized by slowly progressive muscle weakness. Symptoms typically start in early adulthood, with weakness and atrophy in the tibialis anterior muscles and with slow progression over time, which largely spares the quadriceps muscles. Muscle biopsy shows atrophic fibers and rimmed vacuoles without inflammation. Inherited in an autosomal recessive manner, patients with GNE myopathy carry mutations in the GNE gene which affect the sialic acid synthesis pathway. Here, we look at the history and clinical aspects of GNE myopathy, as well as focus on prior treatment trials and challenges and unmet needs related to this disorder.